Short-term improvement in pulmonary hemodynamics is strongly predictive of long-term survival in patients with pulmonary arterial hypertension - Tiede, Henning (University of Chicago Press, 2013)
Abstract. Hemodynamic measurements provide important parameters for determining prognosis and therapy in patients with pulmonary arterial hypertension (PAH). Current guidelines do not incorporate the possible predictive value of individual changes in hemodynamic variables during the disease time course, and there is no consensus about the time point for hemodynamic reevaluation. We aimed to assess the long-term prognostic value of short-term changes in hemodynamic parameters. The study included 122 patients with PAH from the Giessen Pulmonary Hypertension Registry who underwent hemodynamic evaluation at baseline and at 16 weeks (±2.5 standard deviations [SDs]; range: 4–29 weeks) after initial assessment. At baseline, mean pulmonary vascular resistance (PVR) was 1,109 dyn s cm(−5), and 82% of patients were in World Health Organization (WHO) functional class III or IV. Fifty patients died, and 2 underwent lung transplantation during long-term observation (≤10 years; mean: 4.7 years). Kaplan-Meier estimates for transplant-free survival were 93.3%, 76.1%, 57.8%, and 53.1% at 1, 3, 5, and 7 years, respectively. When assigned to prognostic groups, improvements in cardiac output of >0.22 L min(−1) (hazard ratio [HR]: 2.05; [Image: see text]) and a decrease in PVR of >176 dyn s cm(−5) (HR: 1.89; [Image: see text]) at 4–29 weeks were associated with long-term transplant-free survival. Changes in mean pulmonary arterial pressure did not predict long-term prognosis. Of 2 noninvasive parameters assessed in this selected patient group, change in WHO functional class, but not in 6-minute walk distance, predicted long-term prognosis. Short-term assessment of changes in hemodynamic parameters at [Image: see text] after initial invasive evaluation is useful to determine long-term prognosis in patients with PAH.